Diferença e subjetividades do corpo: que educação é essa? - Medeiros, Daniela (2012)
This work was developed for a Postgraduate Program, PPGE / UFSM, in the research line 'Education and the Arts' and offered to discuss: How to think about education and constitution of the body from the difference and their subjectivities? What place and/or between-place this body occupies in school? How the differences of this body have interfere in its constitution? How to think the body involved in these educational processes and subjectivity? The biggest problem, released as the first and interlaced to the others (goals), directs this research that elapses in a post-structuralist perspective and uses, between the different frames, of the theory and Deleuzian philosophy of difference as an important support to think these problematizations. From this, it is proposed to consider the school body and the language producer body in the same manner that the pure thought to the similarities and potential of the body. Such propositions are organized from the stance taken by the methodology chosen, the ABR (Arts-Based Research). This, in turn, allows a written constructed by different possibilities (performatives, literary, musical, poetic and visual) and connect with them as a way to describe every sensation and / or (in) conclusion. Finally, the thoughtful questions throughout the work and anchored in the experiences of an collaborator (Vitor) intersect in a final moment of connections in order to rescue the most that was possible to construct and deconstruct from the proposed - Wich education we are talking about when we consider such thoughts?